AN ANALYSIS OF DEIXIS IN ALADDIN (2019) MOVIE - Ajisoko, Pangkuh; Miza, Mohammad Agha Dhiyahul; Meriry, Laying Ayu; Aprilia, Dinda; Mery, Andi (Borneo Journal of English Language Education, 2020)
This research purpose is exactly to describe the forms of deixis in Aladdin (2019) movie. This research is using qualitative method. The data that are used in this research are totally taken from the dialogues of Aladdin (2019) movie, the data are in form of dialogues, sentences, and words which are analyzed carefully according to the function and classification of each deixis. The sources are available in two forms, first it is a movie (video), and second is the written script of the movie. After analyzing the data, researcher found there are four types of deixis are used in Aladdin (2019) movie, those are person deixis, spatial deixis, social deixis and temporal deixis. Each of deixis has its function and appearances frequency. The data after analyzed shows there are four appearances frequencies have found from this research, first is person deixis 76,56% (1.366), spatial deixis 12,21% (218), social deixis 9,24% (165), and temporal deixis 1,96% (35) those are the appearances frequencies of each deixis. The result found that the most common deixis in Aladdin (2019) movie is person deixis and followed by other deixis below it, in sequence percentages level.